Molecular detection of Sarcocystis aucheniae in the blood of llamas from Argentina - Decker Franco, Cecilia (2016)
Sarcocystis aucheniae are apicomplexan protozoa that infect South American camelids (SACs), giving rise to macroscopic cysts similar to rice grains in skeletal muscles. Visual detection of macrocysts in slaughtered animals hampers commercialization of SAC meat, a highly relevant economic exploitation for Andean rural families. Importantly, the consumption of undercooked S. aucheniae-infested meat causes gastroenteritis. A carnivore definitive host, possibly the dog, acquires the parasite when feeding on infected SAC meat, and later eliminates infective oocysts in its feces. The parasite cycle is completed when SACs ingest contaminated water or pastures. We hypothesized that parasite DNA can be detected in SAC blood using molecular methods. In order to test this hypothesis, a seminested PCR format was specifically designed to target the hypervariable 18S rRNA gene region of S. aucheniae. PCR conditions were optimized using genomic DNA extracted from macrocyst bradyzoites. A detection limit of up to 1 parasite in 10 l of llama blood was established based on DNA samples extracted from aliquots of S. aucheniae bradyzoite-spiked non-infected llama blood. The seminested PCR allowed to detect natural infections of S. aucheniae in llama blood samples originating in the Andean flatlands of Argentina. Specific amplification of S. aucheniae DNA was corroborated by amplicon sequencing. This is the first report of S. aucheniae detection in llama blood, which provides a valuable diagnostic tool for epidemiological studies and for the evaluation of the efficacy of control measures for this parasitosis.